Cross‐protective potential of a live‐attenuated Edwardsiella ictaluri vaccine against Edwardsiella piscicida in channel (Ictalurus punctatus) and channel × blue (Ictalurus furcatus) hybrid catfish. Issue 3 (19th May 2020) - Griffin, Matt J.; Greenway, Terrence E.; Byars, Todd S.; Ware, Cynthia; Aarattuthodiyil, Suja; Kumar, Ganesh; Wise, David J.
Abstract: Edwardsiella piscicida has emerged as an important pathogen of channel × blue catfish hybrids cultured in the southeastern United States. With increasing popularity of hybrid catfish and growing concern over E. piscicida, the crossprotective potential of a live‐attenuated E.ictaluri vaccine was evaluated. An immunization bath of E. piscicida (3 × 10 7 CFU/ml) protected channel catfish against immersion challenge of wild‐type E. ictaluri (1 × 10 7 CFU/ml) across multiple temperatures and feeding regimens (relative percent survival [RPS]: 89–100%). Channel catfish immunized orally with a live‐attenuated E. ictaluri vaccine/feed admix (3 × 10 7 CFU/g of feed) were protected against intracoelomic injections of both high (HD) (7.4x10 5 CFU/fish; RPS = 85%) and low doses (LD) (1.5 × 10 5 CFU/fish; RPS = 88%) of E. piscicida . Because of limited feed consumption during vaccination, oral immunization of hybrids was followed by a 30‐min immersion bath with cultured vaccine (5 × 10 6 CFU/ml). Combinatory oral/bath vaccination was ineffective against HD E. piscicida but was protective against LD E. piscicida (48% RPS) and E. ictaluri (96% RPS). Finally, naïve catfish that survived LD E. piscicida injections were protected against E. ictaluri immersion challenge (2 × 10 7 CFU/ml; RPS: Hybrids 55%; Channels 75%). Results suggest a live‐attenuated E. ictaluri vaccine can also protect channel and hybrid catfish against E. piscicida .